Improving the practice of Competitive Strategies for the protection of Intellectual Property: the law and economics approach - Vladlena LISENCO (Eastern European Journal of Regional Studies)
The article contains analyze of the legal regulation of the protection of intellectual property rights and practice of competitive strategies for the protection of intellectual property using best legal practices of EU countries and Eurasian Economic Union. Legal confirmation of intellectual property right, in fact, means that the state realizes the importance of culture and progress for the preservation and development of society. Protection of the results of creativity, intellectual activity is associated with the protection of individual freedom, human rights. The features of the competitive environment and competitive mechanism in the innovation economy has been analyzed as well as influence of competition on the behavior of economic agents in the innovative economic system. The paper includes analyzes the logic and economics of non-competitive behavior of companies and states in the EU single market and examines the functions of the Directorate of the European Commission for Competition. The EU competition policy tools are flexible and that they take into account the most diverse interests of the single market. The policy of the Eurasian Union as a whole is aimed at the implementation by the member states of measures in competitive policy and contributes to the launch of joint research and industrial projects, allows to increase the competitiveness of products, reduce production costs, ensure joint access to the external market.